CdS Nanoparticles-Decorated Shewanella oneidensis Cells for Ultrafast Photoreduction and Detoxification of Nitrobenzene - Wang, Yan-Zhai; Zhao, Han; Liu, Heng-Chi; Yang, Zhi-Zhi; Yong, Yang-Chun (ACS applied nano materials, 2024)
Nitrobenzene (NB) as essential products and raw materials in industrial production is a highly toxic and prevalent water pollutant that threatens human health and eco-safety. Photocatalytic methods are widely applied in the field of environmental remediation due to their unique photoexcited redox capacity, which provides a great potential for photoreduction of NB. Here, ultrafast photoreduction and detoxification of NB were explored by establishing a biohybrid photocatalytic system with mild biomineralization. It was discovered that the whole-cell hybrid system developed by biomineralization of CdS nanoparticles on the cell surface of Shewanella oneidensis MR-1 (SW) exhibited high photoreduction activity on NB. Strikingly, SW-CdS exhibited a first-order photoreduction rate constant (k) of 1.1 h–1, which was 54 times higher than that with S. oneidensis MR-1 (metabolic reduction). Impressively, this photoreduction rate achieved by SW-CdS was the highest photoreduction rate of NB ever reached by various nanoparticles. In addition, the photoreduction products obtained showed toxicity even lower than that of the traditional reduction product (aniline) for NB detoxification. Further analysis revealed that the biomineralized CdS nanoparticles served as the main catalytical center and contributed to the ultrahigh photoreduction efficiency of SW-CdS. This work provided a simple, ultrafast, and low-toxic method for the photoreduction and detoxification of NB, which would be promising for application in environmental remediation.